Pengaruh Karakteristik Perusahaan Terhadap Luas Pengungkapan Sukarela - Irma Prawita Sari; Yie Ke Feliana; Riesanti Edie Wijaya (Akuntansi dan Teknologi Informasi, 2008)
Disclosure Theory suggest that voluntary disclosure reduces information asymetry among investors by reducing transactions and information cost, which in turn reduces firms' cost of capital. The advantages of voluntary disclosure should encourage the listed firms to present voluntary disclosure besides mandatory disclosure. In fact, many listed firms reluctant to present. Voluntary dimension of corporate disclosure involve the manisfestation of free choice of the firms and its managers. Because of that, the purpose of this study is to reveal factors affecting voluntary disclosure levels for Indonesian firms listed in Jakarta Stock Exchange in 2005 and 2006.